2019
DOI: 10.3238/arztebl.2019.0692
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis and Treatment of Idiopathic Facial Paresis (Bell’s Palsy)

Abstract: Background: Peripheral facial nerve palsy is the most common functional disturbance of a cranial nerve. 60-75% of cases are idiopathic.Methods: This review is based on a selective literature search proceeding from the current, updated German-language guideline on the diagnosis and treatment of idiopathic facial nerve palsy.Results: The recommended drug treatment consists of prednisolone 25 mg bid for 10 days, or 60 mg qd for 5 days followed by a taper to off in decrements of 10 mg per day. This promotes full r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 70 publications
2
96
0
19
Order By: Relevance
“…Patients with incomplete paresis have good prognosis. In contrast, the German and the Spanish guidelines recommend electrodiagnostics for all patients with Bell's palsy [17][18][19]. Some recommend electrodiagnostics for all patients with facial nerve disorder.…”
Section: Electrophysiological Diagnostic Evaluationmentioning
confidence: 99%
“…Patients with incomplete paresis have good prognosis. In contrast, the German and the Spanish guidelines recommend electrodiagnostics for all patients with Bell's palsy [17][18][19]. Some recommend electrodiagnostics for all patients with facial nerve disorder.…”
Section: Electrophysiological Diagnostic Evaluationmentioning
confidence: 99%
“…Idiopathic facial paralysis (also called Bell's palsy) is a peripheral paralysis of the facial nerve of unknown origin, and the most common cause of facial nerve paralysis [4]. Current treatment options include corticosteroids (which have been shown to significantly improve motor recovery [8]), possibly associated with virostatic agents.…”
Section: Commentarymentioning
confidence: 99%
“…From a pathophysiological standpoint, it has been suggested that facial nerve paralysis could result from the reactivation of herpes simplex virus type 1 (HSV-1) infection within the facial nerve [2,3,11] and that as such, episodes of facial paralysis could be provoked by stress (or trauma, e.g. following dental treatment [11]), in analogy to herpes labialis [4]. The present case gives credence to such theory, as idiopathic facial paralysis occurred concurrently with a major anxiety episode secondary to COVID-19-related lockdown and subsequent socio-economical repercussions.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…There may also be decreased tearing, hyperacusis, and/or loss of taste sensation on the anterior two thirds of the tongue. 10 The nerve paralysis was named after Scottish physician, surgeon, and neurologist Charles Bell (1774-1842) who first described the lesions of facial nerve (CN VII) and its clinical presentations. 11 It has been widely accepted that herpes simplex virus and herpes zoster virus are the most common etiology of Bell's palsy.…”
mentioning
confidence: 99%